(untitled) (Spectrum of Humanities and Social Sciences, 2025)
The study measures the visualization of memory and trauma in post-war novels written between 1945 and 1970, on Slaughterhouse-Five and The Naked and the Dead. It’s notable focus on psychological impact after the war. Both writers used stylistic devices. Applying the trauma theory of Cathy Caruth and Dominick LaCapra, the study concerns the psychological stress of war that revealed in literary creations. The study underlines clearly on Kurt Vonnegut’s Slaughterhouse-Five and Norman Mailer’s The Naked and the Dead, evaluated how the experience of trauma is directly and indirectly reflected in people’s identities, mindset and memory. Peoples were highly affected by war physically and mentally. These matters are inter-related as literary policies that mirror the fractured mental states of individuals affected by war. The study interacts with that literature operates which are cultural and sometime individual as well as collective. Main feathers of war are violence, dislocation, loneliness and psychological harm. Over the core reading of storyline techniques, character building, and interesting social phenomena, the study lies on the essential role of literature in bearing witness to historical trauma and facilitating its paradigm over the generations to generation. Eventually, this study tells how post-war novel serves not merely as artistic expression but also as a medium of protection and frequently interpretation of socked as well as unending memory.